Employee Satisfaction And Work-life Balance On Employee Performance: Employee Engagement As Mediation Variable - Riyadi, Bagus Eka; Suhana, Suhana (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2025)
This study aims to examine the influence of Employee Satisfaction and Work-life Balance on Employee Performance at the Pati Regency Transportation Office, with Employee Engagement as a mediating variable. The method used is quantitative with the Partial Least Square Structural Equation Modeling (PLS-SEM) approach. Data was obtained through the distribution of questionnaires to 120 respondents who are State Civil Apparatus (ASN) within the Transportation Office. The results of the study show that Employee Satisfaction and Work-life Balance have a significant positive effect on employee performance. However, Employee Satisfaction has no significant effect on Employee Engagement, while Work-life Balance has a significant effect on Employee Engagement. Employee Engagement also does not significantly mediate the effect of Employee Satisfaction on performance, but has a negative mediating effect on the effect of Work-life Balance on performance. These findings contribute to the literature on human resource management in the public sector and become the basis for formulating policies to improve the performance of civil servants through strategies to increase job satisfaction and work-life balance.